A Case Study: Integration of Local Wisdom in the Implementation of the Merdeka Curriculum at Elementary School - Damayanti, Nora Sara (Universitas Trunojoyo Madura, 2025)
The implementation of the Merdeka Curriculum is the government’s effort to create learning that is more contextual, flexible, and student-centered in order to meet the challenges of 21st-century education. This study aims to describe how the Merdeka Curriculum is implemented at SDN Gumuksari 02 and how it influences the classroom atmosphere and students’ character.The Merdeka Curriculum provides teachers with the flexibility to design learning activities that align with the students’ conditions and needs, including incorporating local wisdom values such as village culture and agricultural activities. This research employs a descriptive qualitative method with classroom teachers as the main subjects. Data were collected through interviews, documentation, and observation, and then analyzed in depth to identify successes, obstacles, and strategic solutions in its implementation. The results of the study show that despite certain challenges, the implementation of the Merdeka Curriculum has succeeded in creating a more active and meaningful learning environment for students. This research contributes to strengthening cultural identity and enhancing student engagement in contextual, meaningful learning that is aligned with their socio-cultural environment.